Use of the Tailored Activities Program to reduce neuropsychiatric behaviors in dementia: an Australian protocol for a randomized trial to evaluate its effectiveness. (May 2014) - O'Connor, C. M.; Clemson, L.; Brodaty, H.; Jeon, Y. H.; Mioshi, E.; Gitlin, L. N.
ABSTRACT Background: Behavioral and psychological symptoms of dementia (BPSD) are often considered to be the greatest challenge in dementia care, leading to increased healthcare costs, caregiver burden, and placement into care facilities. With potential for pharmacological intervention to exacerbate behaviors or even lead to mortality, the development and rigorous testing of non-pharmacological interventions is vital. A pilot of the Tailored Activities Program (TAP) for reducing problem behaviors in people with dementia was conducted in the United States with promising results. This randomized trial will investigate the effectiveness of TAP for reducing the burden of BPSD on persons with dementia and family caregivers within an Australian population. This trial will also examine the cost-effectiveness and willingness to pay for TAP compared with a control group. Methods: This randomized trial aims to recruit 180 participant dyads of a person with dementia and their caregivers. Participants will have a diagnosis of dementia, exhibit behaviors as scored by the Neuropsychiatric Inventory, and the caregiver must have at least 7 h per week contact. Participants will be randomly allocated to intervention (TAP) or control (phone-based education sessions) groups, both provided by a trained occupational therapist. Primary outcome measure will be the revised Neuropsychiatric Inventory – Clinician rating scale (NPI-C) to measure BPSD exhibited by the person with dementia. Conclusions: This trial investigates the effectiveness and cost-effectiveness of TAP within an Australian population. Results will address a significant gap in the current Australian community-support base for people living with dementia and their caregivers.